Ekonomi Politik Media Penyiaran: Rivalitas Idealisme Nilai Islami dan Mekanisme Pasar - Gun Gun Heryanto (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2017)
Broadcast television in Indonesia increasingly prevalent with various packaging program specifically religious character of Islamic events. The programs are varied, ranging from reality shows, soap operas, talk shows, comedy, religious lectures and others. Gait television stations keislama program includes phenomena on one side commendable. Because it could be, exposure (exposure) of a religious program a chance to form a strong impact in most Muslim audiences for media to apply the principles konsonansi. This paper discusses the political economy television relation to public space and the ideals of the Islamic program.